Assemblage organization of surface-active arthopods in Sonoran Desert dune ecosystems - Crawford, Clifford S. (Instituto de Ecología, A.C., 1989)
I tested the hypothesis, in northwestern Sonora, thet temporal patterns of organization among surface-active arthropods resemble each other in dune and interdune habitats from coastal (Puerto Peñasco) and inland (Gran Desierto) dune ecosystems. Seasonal (October and May) counts of arthropods at 12-h intervals were made from pitfall-trap grids at both sites. Although the coastal interdune had the greatest plant cover (32%) rarefaction analysis showed its expected species richness of arthropods, E(Sn), to be similar to richness in the inland interdune. In both interdune habitats, E(Sn) was significantly greater in spring then fall, and generally much greater then in dune habitats. Both E(Sn) and trap-capture frequencies averaged higher at night than during the day in all habitats. Values of Hill's N2 diversity and Hill's modified E5 evenness in coastal and inland interdune assemblages were similar at night in spring. Otherwise, few correlations involving habitat, season, and diel time were evident, except that evenness was usually greatest at night. Neither plant cover nor recent precipitation at the coast were correlated with species richness. Species turnover (Sorensen's Index) was greater between inland habitats then between interdune habitats when sites were compared. Overall, evidence for consistent resemblance in assemblage organization between similar habitats-specially dunes-over seasonal and diet time was not strong.